DETERMINING THE DISTANCE TO THE TARGET IN PASSIVE RADAR OF SURFACE OBJECTS - I. M. Mytsenko; O. M. Roenko (Radio Physics and Radio Astronomy)
Subject and Purpose. While outperforming active radar methods for range, stealth, and energy consumption, passive radar has a significant disadvantage: it cannot determine the target distance and coordinates when only one reference receiving point is available. We seek to develop a passive radar method and technical means for its implementation to establish the target distance over the sea surface with a single reference receiving point.